2010
DOI: 10.1093/jac/dkq491
|View full text |Cite
|
Sign up to set email alerts
|

Spread of Escherichia coli O25b:H4-B2-ST131 producing CTX-M-15 and SHV-12 with high virulence gene content in Barcelona (Spain)

Abstract: We report for the first time the clonal spread of SHV-12-producing O25b:H4-B2-ST131 isolates characterized by high virulence gene content. Moreover, we describe the distribution of the ST131 isolates within different virulence groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 33 publications
9
49
4
1
Order By: Relevance
“…A similar fraction of ST131 among ESBL isolates was found in several international studies (24)(25)(26) and in a recent Danish study that, in contrast to our study, provided only limited characterization of the isolates (27).…”
Section: Discussionsupporting
confidence: 90%
“…A similar fraction of ST131 among ESBL isolates was found in several international studies (24)(25)(26) and in a recent Danish study that, in contrast to our study, provided only limited characterization of the isolates (27).…”
Section: Discussionsupporting
confidence: 90%
“…This contrasts with the 9% prevalence of ST131 among the 92 analyzed ESBLEC isolates from a similar study from 2004 done in 11 Spanish hospitals (7 of which were included in the present study) (8). More recent studies found even higher prevalences of O25b-ST131 among ESBLECs in various Spanish cities, including Lugo in 2008 (23%) (5) and in 2012 (61%) (27), Barcelona (32% in 2008) (28), Seville (13% in 2010) (29), and Madrid (21% in 2008) (30). Other countries have also had high reported prevalences of ST131 among the ESBLEC strains, including Denmark (38%) (31), Japan (41%) (32), the United States (47%) (33), and Canada (78%) (34).…”
Section: Discussioncontrasting
confidence: 80%
“…In contrast, other studies have found that ST131 is not highly virulent in infection models and that it differs from classical ExPEC group B2 strains by the absence of several virulence genes, such as hlyA and cnf1 (38). It appears that few virulence genes are consistently present in this clone (39).…”
Section: Discussioncontrasting
confidence: 67%